Hypoglycemia in Patients with Type-2 Diabetes Mellitus Nephropathy - Faheem Ur Rahman; Sumayya Rahman; Iqbal Haider; Nayab Munib; Wazir Mohammad Khan (Aziz Fatimah Medical and Dental College, 2023)
Objective: To find out the frequency of hypoglycemia in Type-2 Diabetics having nephropathy Methodology: This cross-sectional observational study was carried out in Medical Teaching Institute Khyber Teaching Hospital. Department of Medicine, from August 21, 2020, to January 21, 2021. Two-hundred and eighty-one (281) patients with Type 2 diabetic nephropathy were observed in due course and were subjected to detailed history and examination. A sample of 5 ml venous blood was obtained from the patients to measure blood glucose levels to detect hypoglycemia. Experienced pathologists analyzed all investigations. Results: The mean ± Standard deviation (SD) of age in this study was 60± 10.26 years. Female patients outnumbered males in this study. Hypoglycemia was reported in 21% of patients while 79% did not have hypoglycemia. Conclusion: Type-2 diabetics having nephropathy are prone to hypoglycemia. These patients should be carefully observed for clinical and biochemical features of hypoglycemia .